Discharging behavior of a fixed-bed thermochemical reactor under different charging conditions: modelling and experimental validation - Wang, C; Ma, H; Ahmad, A; Yang, H; Ji, M; Zou, B; Nie, B; Chen, J; Tong, L; Wang, L; Ding, Y (MDPI, 2022)
Thermochemical heat storage has attracted significant attention in recent years due to potential advantages associated with very high-energy density at the material scale and its suitability for long-duration energy storage because of almost zero loss during storage. Despite the potential, thermochemical heat storage technologies are still in the early stage of development and little has been reported on thermochemical reactors. In this paper, our recent work on the charging and discharging behavior of a fixed-bed thermochemical reactor is reported. Silica gels were used as the sorbent for the experimental work. An effective model was established to numerically study the effect of different charging conditions on the discharging behavior of the reactor, which was found to have a maximum deviation of 10.08% in terms of the root mean square error compared with the experimental results. The experimentally validated modelling also showed that the discharging temperature lift increased by 5.84 times by changing the flow direction of the air in the discharging process when the charging level was at 20%. At a charging termination temperature of 51.25 °C, the maximum discharging temperature was increased by 2.35 °C by reducing the charging flow velocity from 0.64 m/s to 0.21 m/s. An increase in the charging temperature and a decrease in the air humidity increased the maximum discharging outlet temperature lift by 3.37 and 1.89 times, respectively.